Sistem Informasi Stok Barang Gudang MAMA Mart Berbasis Web - Hilmi, Ifham; Latifa, Alfina; Heni Pertiwi, Dilla; Subhiyanto; Kasoni, Dian (LPPM STMIK ANTAR BANGSA, 2025)
Abstract—This web-based warehouse stock information system is designed to make it easier to manage and monitor stock of goods at the Mama Mart Warehouse efficiently and integrated. The system allows users to record, monitor, and update inventory data in real-time, minimizing human error and improving inventory accuracy. The system is built using modern web technology by adopting the Laravel framework for the backend and Bootstrap for the frontend, providing optimal performance and a responsive display. MySQL is used as a database management system to store all data related to stock of goods, including information about the number of incoming goods, outgoing goods, and remaining available stock. The main features of this system include Stock Data where Users can add, update, and delete item data in the warehouse, including details such as item name, item code, category, and stock quantity. Then there is Report and Monitoring where the System provides a complete report related to the movement of stock of goods, including the history of incoming and outgoing goods, as well as notifications for stock of goods that are close to the minimum limit. There is a User, namely the system supports the management of users with various levels of access, so that only users who have certain authority can make changes to stock data. And Search and Filter: Users can easily search and filter item data based on various criteria such as item name, category, and transaction date. Keywords: Information Systems, Stock of Goods, Warehouse